2010
DOI: 10.1177/145507251002700304
|View full text |Cite
|
Sign up to set email alerts
|

Life Experience and Alcohol: 60–75-year-olds’ Relationship to Alcohol in Theme Interviews

Abstract: The article describes drinking habits of Finnish older adults and their relationship to alcohol. The study is based on the analysis of theme interviews among 60-70-year-old urban people. The method was biographical, qualitative content analysis. Alcohol consumption of the older adults was investigated through the analysis of changes in the use of alcohol during life course and the features of current drinking habits. The article argues that events of both life course and changing Finnish alcohol culture have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 4 publications
1
31
0
Order By: Relevance
“…Ethnicity was not reported in other studies. Only 5 studies reported SES of participants or a proxy [ 16 20 ]. Of these one recruited from predominantly high socioeconomic areas [ 19 ], the other studies included a range of socioeconomic groups, none specifically recruited people from low SES groups ( S3 File ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ethnicity was not reported in other studies. Only 5 studies reported SES of participants or a proxy [ 16 20 ]. Of these one recruited from predominantly high socioeconomic areas [ 19 ], the other studies included a range of socioeconomic groups, none specifically recruited people from low SES groups ( S3 File ).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies appeared to include participants drinking at a range of levels, though this was sometimes not clearly reported. A number of studies included some abstainers, including past drinkers [ 9 , 10 , 18 , 20 22 ]; one study reported excluding lifetime abstainers [ 20 ]. Two papers using the same study participants clearly reported the distribution of drinking patterns of participants [ 9 , 10 ] and included occasional minimal drinkers, moderate and heavy drinkers, currently abstinent previously dependent drinkers and a small number of dependent drinkers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has suggested that age-specific practices required to meet the needs of older people, in relation to alcohol consumption, and draw them into treatment are poorly understood[ 18 ]. However research on alcohol consumption in older adults is still relatively scarce, there are notably few quantitative studies and no qualitative studies investigating support for alcohol related health issues in older people[ 9 ][ 10 ][ 19 21 ]. Therefore this research contributes to the limited body of in-depth qualitative evidence regarding the issues surrounding alcohol consumption in mid to later life.…”
Section: Introductionmentioning
confidence: 99%